A Case of Delayed Hepatic Injury Associated with Teriflunomide Use as Assessed for Causality Using the Updated RUCAM. (15th June 2022) - Wurzburger, Riana
Abstract : Teriflunomide is a pyrimidine synthesis inhibitor used in the treatment of multiple sclerosis that has in rare instances been associated with liver toxicity, though there are few documented cases. Here, we report a case of probable teriflunomide-induced liver injury as assessed for causality using the updated RUCAM. The liver injury occurred approximately nine months after teriflunomide initiation and improved with discontinuation of the drug and treatment with cholestyramine.